Optical Properties and Radiation Stability of Magnesium Silicate - Harutyunyan, V. V.; Badalyan, A. O.
A microwave (MW) method of hydrothermal synthesis of magnesium silicate is developed. At low temperature (240 0C), nuclei of crystalline phase of магний silicate are obtained. Some optical characteristics of the synthesized product are determined. Based on, X-ray and thermographic studies are revealed that the synthesis of magnesium silicate from water-soluble salts of initial components in microwave ovens promotes the formation of magnesium at lower temperatures. MW synthesis of magnesium silicate ensures obtaining of nanosized powder after heat treatment at 850 0C.
Keywords: Physics